Perancangan Smart Server System Berbasis Monitoring Suhu, Kelembapan, dan Keamanan Akses di CV Gundara Solusi Bersama Ungaran - Aizaas Vianansa Rochmawan; Priyadi Priyadi; Candra Supriadi (STEKOM PRESS, 2026)
Server rack management at CV Gundara Solusi Bersama Ungaran previously relied on conventional room cooling and manual door locking mechanisms without environmental monitoring and access logging. This condition increases the risk of hardware overheating, excessive humidity, and unauthorized physical access. This study proposes a Smart Server System based on the ESP32 microcontroller to integrate temperature and humidity monitoring, automatic thermal control, electronic access security, and cloud-based logging within a single Internet of Things (IoT) platform. The system utilizes an SHT21 sensor, dual DC cooling fans controlled through a relay module, a 4×4 keypad for PIN authentication, a solenoid door lock, an LCD 20×4 I2C display, and Google Sheets integration through an HTTPS REST API. The cooling mechanism activates automatically when the temperature exceeds 27°C or humidity exceeds 65% RH, while access events are recorded in real time to cloud storage. The system was developed using an iterative Research and Development (R&D) prototyping approach and evaluated through functional, performance, and reliability testing. Experimental results show that the proposed system achieved a temperature measurement MAE of 0.220°C, humidity MAE of 0.724% RH, average response times below 3 seconds for cooling and access control operations, logging completeness of 100%, and system uptime of 99.7% during a 72-hour continuous test. The proposed system provides an affordable and integrated solution for thermal management and physical security monitoring of server infrastructure in small and medium enterprises (SMEs).